Piezoelectric properties of Pb[Zr0.45Ti0.5-xLux(Mn1/3Sb2/3)(0.05)]O-3 ceramics - Yoon, SJ; Kang, HW; Kucheiko, SI; Kim, HJ; Jung, HJ; Lee, DK; Ahn, HK (WILEY-BLACKWELL, 1998)
The piezoelectric properties of Pb[Zr0.45Ti0.5-xLux(Mn1/3Sb2/3)(0.05)]O-3 ceramics, with 0 less than or equal to x 0.03, have been investigated. The partial substitution of Ti4+ with Lu3+ permitted improvement of the electromechanical coupling factor (k(p)), the dielectric constant (epsilon(33)(T)), and the piezoelectric constant (d(33)), while the dielectric loss (tan delta) increased and the mechanical quality factor (Q(m)) decreased with an increase of x, A pertinent piezoelectric material for actuator applications was Pb[Zr0.45Ti0.48Lu0.02(Mn1/3Sb2/3)(0.05)]O-3, and the piezoelectric properties were k(p) = (58.5 +/- 0.5)%, epsilon(33)(T) = 32 +/- 25, d(33) = (373 +/- 6) x 10(-12) C/N, Q(m) = 714 +/- 22, and tan delta = (0.98 +/- 0.03)%.